224 Exposure to polycyclic aromatic hydrocarbons and sperm quality of coke-oven workers. (11th October 2013) - Lin, W Y; Jeng,; Pan,; Yu, M L; Dai, C Y; Li, C H; Chang, N C; Huang,; Hsieh, M H; Yang, J F; Wang, C L; Huang, C F; et al.
Abstract : Objectives: The study aimed to assess whether exposure to polycyclic aromatic hydrocarbons (PAHs) alter sperm quality of coke-oven workers. Methods: Personal breathing zone, urine, and semen samples were collected from nonsmoking workers at top-side ovens (high exposure, N = 16) and side-ovens (low exposure, N = 20), and administrative staff members serving as the control group (N = 15). PAH concentrations were analysed by a gas chromatography quadruple spectrometer. Routine semen was analysed by procedures in accordance with the World Health Organization guidelines. Urinary 1-hydroxypyrene (1-OHP) was analysed by HPLC with a fluorescence detector. Results: ANOVA analysis showed a significant difference in urinary 1-OHP levels (14.7 ± 12.9, 4 ± 4.3, 0.3 ± 0.2 g/g creatinine respectively, p = 0.02) between the exposed groups and the control. Mean concentrations of 16 species of PAHs significantly differed among the three groups (Total PAHs = 41620.3 ± 17697.6 ng/m 3, 19887.6 ± 1378.1 ng/m 3, 57.0 ± 18.1ng/m 3, p < 0.0001; Benzo (g, h, i)perylene = 3553.9 ± 1250.7 ng/m 3, 3001.9 ± 1367.7 ng/m 3, 2.0 ± 1.5 ng/m 3, p < 0.0001, p = 0.067). Asthenospermia was found more frequently in the high exposure group as compared to the control (37.5% and 13.3%, respectively, p < 0.01). The exposed groups had lower percentages of normal morphology as compared with the control group (14.5 ± 3.4%, 15.0 ± 3.1%, 34.5 ± 2.6% p < 0.01). Multiple regression analysis showed that PAH species positively correlated with abnormality of morphology and motility of sperm. Conclusion: Abnormal morphology of sperm was associated with PAH concentrations, especially those with heavy molecular weights, e.g. benzo (g, h, i)perylene and benzo (k)fluoranthene.